Duloxetine, Gabapentin, and the Risk for Acute Myocardial Infarction, Stroke, and Out-of-Hospital Death in Medicare Beneficiaries With Non-Cancer Pain. Issue 5 (11th May 2023) - Corriere, Meghan A.; Dickson, Alyson L.; Daniel, Laura L.; Nepal, Puran; Hall, Kathi; Plummer, W. Dale; Dupont, William D.; Murray, Katherine T.; Stein, C. Michael; Ray, Wayne A.; Chung, Cecilia P.
Abstract : Objective: Duloxetine is a serotonin-norepinephrine reuptake inhibitor prescribed for musculoskeletal and other forms of chronic pain. Its dual pharmacologic properties have the potential to either raise or lower cardiovascular risk: adrenergic activity may increase the risk for acute myocardial infarction (AMI) and stroke, but antiplatelet activity may decrease risk. Gabapentin is another nonopioid medication used to treat pain, which is not thought to have adrenergic/antiplatelet effects. With the current emphasis on the use of nonopioid medications to treat patients with chronic pain, assessing cardiovascular risks associated with these medications among high-risk patients is important. Materials and Methods: We conducted a retrospective cohort study among a 20% sample of Medicare enrollees, aged 65 to 89, with chronic pain who were new users between 2015 and 2018 of either duloxetine (n = 34, 009) or gabapentin (n = 233, 060). We excluded individuals with cancer or other life-threatening conditions at study drug initiation. The primary outcome was a composite of AMI, stroke, and out-of-hospital mortality. We adjusted for comorbidity differences with time-dependent inverse probability of treatment weighting. Results: During 115, 668 person-years of follow-up, 2361 patients had the composite primary outcome; the rate among new users of duloxetine was 16.7/1000 person-years compared with new users of gabapentin (21.1/1000 person-years), adjusted hazard ratio = 0.98 (95% CI: 0.83, 1.16). Results were similar for the individual components of the composite outcome as well as in analyses stratified by demographic and clinical characteristics. Discussion: In summary, cohort Medicare patients with non-cancer pain beginning treatment with duloxetine had rates of AMI, stroke, and out-of-hospital mortality comparable to those who initiated gabapentin.